National Parks and Protected Areas - Yang, Rui; Cao, Yue; Carver, Steve; Yu, Le (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on fundamental and applied research on national parks and protected areas. The destruction and degradation of nature undermine biodiversity and human well-being. Protected areas (including national parks) represent one of the best ways to safeguard nature and preserve biodiversity for the benefit of all life on Earth. Protected areas put the focus on nature conservation while providing various types of ecosystem services and contributing to the achievement of the Sustainable Development Goals (SDGs). In this reprint, special attention is given to wilderness quality, connectivity conservation and ecological networks, ecosystem services, community participation, tourism and other relevant topics.